Sapatos ni Lola an assistive alert device for the dependent elderly aged 70 and above living with their family inside urban communities in the Philippines - Narvaez, Angeli Marie G.
The Filipinos have always been protective of life, especially of the elderly because they served as our leaders and mentors. But as these people grow older, they acquire disabilities and diseases which weakens their response, reflex, and movement and makes them highly dependent. Aside from that, accidents due to the acquired disabilities and diseases also causes injuries and even death. But dependency takes too much freedom and adults feel very much uncomfortable being closely watched. This study proposes a portable automatic alert system which immediately calls for assistance for the elderly to a nearby relative or caretaker when they fall, or lose consciousness inside their homes. By studying the lifestyle of the elderly inside an urban community, a transmitter-receiver alert device is designed to fit the need of fast response in case of emergency.